2012
DOI: 10.1007/s10633-012-9349-7
|View full text |Cite
|
Sign up to set email alerts
|

Motion and pattern cortical potentials in adults with high-functioning autism spectrum disorder

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Autism Spectrum Disorder (ASD) is a condition in which visual perception to both static and moving stimuli is altered. The aim of this study was to investigate the early cortical responses of subjects with ASD to simple patterns and moving radial rings using visual evoked potentials (VEP). Permanent repository link MethodsMale ASD participants (n=9) and typically developing (TD) individuals (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Since this finding, several studies have confirmed superiority in the Embedded Figures Task in both children and in adults on the spectrum – although functional imaging suggest the advantage for the Embedded Figures Task lies within the primary visual cortex rather than higher cortical areas . While visual evoked potentials to pattern reversal high and low contrast chequer boards are not different in ASD adults, there are differences in the responses to higher‐order motion stimuli . More recent work has highlighted a difference to low contrast drifting gratings in V1 suggesting that there may be altered contrast gain control or suppression in V1 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this finding, several studies have confirmed superiority in the Embedded Figures Task in both children and in adults on the spectrum – although functional imaging suggest the advantage for the Embedded Figures Task lies within the primary visual cortex rather than higher cortical areas . While visual evoked potentials to pattern reversal high and low contrast chequer boards are not different in ASD adults, there are differences in the responses to higher‐order motion stimuli . More recent work has highlighted a difference to low contrast drifting gratings in V1 suggesting that there may be altered contrast gain control or suppression in V1 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other reported no differences in the properties of the P100 using pattern reversal with low spatial frequencies gratings in adults (Jemel 2010, Constable 2012, suggesting a specific deficit in processing high frequencies. While all those studies varied by different experimental settings, levels of attention required and also age range tested, they converged to an abnormal spatial frequency processing in ASD (see also pei 2014pei , Milne 2009b) that has contributed to the development of the weak central coherence hypothesis (Frith, 1989) and the enhanced perceptual functioning hypothesis (Mottron et al,2006) of ASD.…”
Section: N135mentioning
confidence: 94%
“…Visual responses generated by the prestriate and striate visual cortices have been shown to be affected in children and adults with ASD when participants were presented with gabor patches, black and white patterns, gratings or other simple shapes (Milne et al 2009b;Constable et al 2012;Vandenbroucke et al 2008;Pei et al 2014;Baruth et al 2010;Takarae et al 2014).…”
mentioning
confidence: 99%
“…ASD and ADHD often present as co-occurrence in children ( Russell et al, 2014 ; Mansour et al, 2017 ) as well as other co-occurrences of conditions such as anxiety, epilepsy, and sleep disorders ( Bougeard et al, 2021 ). Visual perception in ASD shows superiority in visual search ( Constable et al, 2020a ) and abnormal electrophysiological cortical differences in global motion perception ( van der Hallen et al, 2019 ), motion onset ( Constable et al, 2012 ), and coherence thresholds perception ( Robertson et al, 2014 ). For reviews of sensory and visual perception in ASD see Dakin and Frith (2005) and Robertson and Baron-Cohen (2017) .…”
Section: Introductionmentioning
confidence: 99%